Does four weeks of simple reaction time training improve start performance in swimming? - Lepretre, P.-M.; Kazarine, L.; Puel, F.; Chollet, D.; Fernandes, R. J. P. (XIIth International Symposium for Biomechanics and Medicine in Swimming, 2014)
Background: Start performance, as defined by time to 15-m, has been used as an indicator of overall performance in sprint swimming. However, there is limited information regarding the key time to response to start (RT) that influence swimming start performance. The aim of this study was to investigate the effect of RT training on start performance in sprint swimming trials. Methods: Eight male French national sprint swimmers (17.5±0.9years, 174.0±0.1cm, 65.6±10.4kg) performed, before and after 4 weeks of training, 3 repetitions of squat jump (SJ), counter movement jump (CMJ) and start on swimming start block on a Microgate Optojump optical measurement system. Short-term training session consisted to plyometric session associated to 3 days a week, a swimming start training based on simple reaction time with different stimuli: visual, auditory, combined (visual and auditory). Results: Pearson correlation revealed time to perform 15-m was inversely related with height performance in SJ (r=-0.82, p=0.013) and CMJ (r=-0.85, p=0.007) after but not before training (SJ: r=- 0.61, p=0.111; CMJ: r=-0.60, p=0.113). Time to perform 15-m was significantly related toRT measured on the block during auditory swimming start before (r=0.89, p=0.019) and after training session (r=0.83, p=0.022). No significant relationship was found between the change in RT and the difference in the time to perform 15-m with training (r=0.61, p=0.109). Finally, there was no significant change in 15-m swimming start (before training: 6.81±0.56s vs. after training: 6. 74±0.50s) with a small Effect size (Cohen's d: 0.13). Conclusion: This study provides start training with stimuli associated to plyometric training induced neuromuscular adaptations rather than strength improvement, which was directly transferable in swimming start condition.